INFORMATION TECHNOLOGY FOR EXPERT EVALUATION PROCESSING IN SCENARIO ANALYSIS OF SUBJECT DOMAIN - Фисун, Николай; Кандыба, Игорь (SWorldJournal, 2021)
The paper considers methods of expert estimation, which are necessary for implementation of information technology of prediction of university admission campaign. The features of Delphi method implementation for expert evaluation of characteristics of pr